2020
DOI: 10.1177/1934578x20953955
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Essential Oil FromTetradenia ripariaand Its Attractant Activity for Mediterranean Fruit Fly,Ceratitis capitata

Abstract: The Mediterranean fruit fly or medfly, Ceratitis capitata (Wiedemann) (Diptera: Tephritidae), is one of the most economically important invasive pests worldwide, with over 300 known hosts. Essential oils have great promise for application in integrated pest management, where they function as natural repellents, attractants, and toxicants with a reduced impact on the environment. In this study, we evaluated essential oil from aerial parts of the African ginger bush, Tetradenia riparia (Hochst.) Codd (Lamiaceae)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 28 publications
(48 reference statements)
3
24
0
1
Order By: Relevance
“…In short-range attraction bioassays with male C. capitata , there were significant differences in behavioral response to the five essential oil treatments ( F = 8.509; df = 4,20; p < 0.001; Figure 2 ). As seen in previous studies [ 44 , 45 , 46 , 47 ], highest attraction was observed with TTO (tea tree oil) [ 44 ]. Attraction to MCEO was comparable to that observed with TREO ( Tetradenia riparia essential oil), a strong attractant [ 46 ], but also comparable to that observed with BTEO (blue tansy essential oil), a milder attractant [ 47 ].…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…In short-range attraction bioassays with male C. capitata , there were significant differences in behavioral response to the five essential oil treatments ( F = 8.509; df = 4,20; p < 0.001; Figure 2 ). As seen in previous studies [ 44 , 45 , 46 , 47 ], highest attraction was observed with TTO (tea tree oil) [ 44 ]. Attraction to MCEO was comparable to that observed with TREO ( Tetradenia riparia essential oil), a strong attractant [ 46 ], but also comparable to that observed with BTEO (blue tansy essential oil), a milder attractant [ 47 ].…”
Section: Resultssupporting
confidence: 75%
“…As seen in previous studies [ 44 , 45 , 46 , 47 ], highest attraction was observed with TTO (tea tree oil) [ 44 ]. Attraction to MCEO was comparable to that observed with TREO ( Tetradenia riparia essential oil), a strong attractant [ 46 ], but also comparable to that observed with BTEO (blue tansy essential oil), a milder attractant [ 47 ]. However, attraction to MCEO was significantly greater than that observed with MGEO (mastic gum essential oil), a weak attractant [ 45 ], and significantly less than that observed with TTO, the best essential oil attractant identified to date [ 44 , 45 , 46 , 47 ].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The source of insects, rearing protocols and experiment design for laboratory bioassays were as described previously. [25][26][27] All observations were carried out at room temperature in small collapsible cages (20.3 × 20.3 × 20.3 cm) into which 50 flies were introduced 1 hour prior to the start of each experiment. Tests were initiated by introducing a Petri dish (53 mm diameter × 12 mm height) with a filter paper disk containing a sample of essential oil (10 µL of a 10% dilution in acetone).…”
Section: Short-range Attraction Bioassaysmentioning
confidence: 99%
“…In recent years, reduced-risk agents such as essential oils and natural ("green") volatile compounds have gained increased recognition as key elements for improving integrated pest management strategies. 8,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Tanacetum annuum L. (synonyms: Balsamita annua L., B. multifida Clemente, and Chrysanthemum annuum [L.] Fiori) is a member of the giant family of Asteraceae (Compositae). Members of the genus Tanacetum have been used for medicinal purposes for decades due to their wide range of pharmacological and chemical properties as well as excellent medicinal values.…”
mentioning
confidence: 99%